First isolation of Leptospira borgpetersenii from Fetuses of Wild boars (Sus scrofa) - Brihuega, Bibiana Felicitas (2017)
Leptospirosis is a worldwide zoonose and is endemic in many countries. This zoonosis is maintained in nature by chronic renal infection of carrier animals, being rodents and other small mammals the most important reservoirs. Also, significant sources of human infection are domestic animals, such as livestock and dogs. The wild boar (Sus scrofa) is an introduced species from Europe which is widespread in America and particularly in the Center and South of Argentina. This species is highly valued by hunters in the region and their meat is consumed more often. In many countries of the world (Europe, USA and Australia) studies of seroprevalence have been carried out, the seroreactivity does not mean that the wild boar has clinical symptoms of leptospirosis or that wild boars are maintenance host of this pathogen. However, these animals have been in contact to leptospiras in their environment in the past. This study has the objective of molecular characterization of pathogenic Leptospira sp. isolated strain obtained from fetuses of wild boars from Patagonia Argentina. Four fetuses were aborted from a wild boar (Sus scrofa) in Patagonia, the southern region of Argentina. Necropsy was performed of the 4 fetuses and samples of kidneys, liver, spleen and lung were cultivated in Fletcher and EMJH mediums. Also, samples of liver, spleen, lung and kidney of fetuses were processed and analyzed by direct immunofluorescence. Multiple Locus Variable number tandems repeats Analysis (MLVA) was used to characterize the isolated strain. The genetic profile of the isolated pathogenic Leptospira sp. strain was identical to the profile of Leptospira borgpetersenii serovar Castellonis Castellon 3. To the best of our knowledge this is the first isolation of Leptospira spp. from a wild boar fetus.